Differential Expression of IFN-γ, IL-10, TLR1, and TLR2 and Their Potential Effects on Downgrading Leprosy Reaction and Erythema Nodosum Leprosum - Douglas Eulálio Antunes; Isabela Maria Bernardes Goulart; Mayara Ingrid Sousa Lima; Patrícia Terra Alves; Paula Cristina Brígido Tavares; Luiz Ricardo Goulart (Journal of Immunology Research)
Leprosy reactions are acute immunological events that occur during the evolution of chronic infectious disease causing neural damage and disabilities. A study using blood samples of 17 leprosy reaction patients and 17 reaction-free was carried out by means of associations between antigens, receptors, and expression of cytokines, using path analysis providing new insights into the immunological mechanisms involved in triggering leprosy reactions. Toll-like receptors (TLR) such as TLR1 and TLR2, presented balanced expression in the reaction-free multibacillary (MB) group (TLR1: 1.01±0.23, TLR2: 1.22±0.18; p=0.267). On the other hand, downgrading type 1 reaction (T1R) (TLR1: 1.24±0.17, TLR2: 2.88±0.37; p=0.002) and erythema nodosum leprosum (ENL) (TLR1: 1.93±0.17, TLR2: 2.81±0.15; p=0.004) revealed an unbalance in relation to the expression of these receptors. When the path analysis was approached, it was noted that interleukin 10 (IL-10) expression showed a dependence relation with phenolic glycolipid I (PGL-I) in downgrading T1R (direct effect=0.503>residual effect=0.364), whereas in ENL, such relationship occurred with lipoarabinomannan (LAM) (direct effect=0.778>residual effect=0.280). On the contrary, in the reaction-free leprosy group, interferon-gamma (IFN-γ) levels were dependent on the association between TLR2 and TLR1 (0.8735). The high TLR2 expression associated with IL-10 levels, in the leprosy reaction groups, may be hypothetically related to the formation of TLR2/2 homodimers and/or TLR2/6 heterodimers linked to evasion mechanisms in downgrading reactions and pathophysiology of ENL.